Reformulation of the Law on the Rights of Apartments Built on Waqf Land as an Effort to Synchronize Land Regulations and Waqf Regulations - Wahyu Utami, Widya; Redi, Ahmad (Greenation Publisher & Yayasan Global Resarch National, 2025)
Regulations regarding flats built on waqf land still face various legal problems, especially related to the synchronization between land and waqf regulations. The disharmony of these legal norms creates uncertainty in terms of ownership, utilization, and legal status of the flats. This study aims to reformulate the legal construction that can bridge the dualism of regulations between agrarian law and waqf law, thus producing a more integrative, fair legal system that provides legal certainty for all interested parties. The approach used in this study is a normative approach with comparative analysis and a conceptual approach. This legal reformulation is expected to be the basis for the new legal policy formulation that is adaptive to the development of community needs, especially in the provision of waqf-based housing.